Climate Change in the Northwest Implications for Our Landscapes, Waters, and Communities - Dalton, Meghan M.; Mote, Philip W.; Snover, Amy K. (NCA Regional Input Reports,, 2013)
Prepared for the 2013 National Climate Assessment and a landmark study in terms of its breadth and depth of coverage, Climate Change in the Northwest is the result of collaboration among numerous local, state, federal, and nongovernmental agencies to develop a comprehensive, state of the art look at the effects of climate change on Washington, Oregon, and Idaho. The Northeast is already experiencing the impacts of a changing climate, and will likely continue to experience warming temperatures, more extreme precipitation events, reduced snow and ice cover and rising relative sea levels. The book presents a review of the historic, current, and the projected future climate of the region; describes interactions with important sectors of the Northeast and examines cross-sectoral issues, namely climate change mitigation, adaptation, and education and outreach. Rich in science and case studies, it examines the latest climate change impacts, scenarios, vulnerabilities, and adaptive capacity and offers decision makers and stakeholders a substantial basis from which to make informed choices that will affect the well-being of the region's inhabitants in the decades to come.